Coprophagy in moose - Spitzer, Robert; Åström, Cecila; Felton, Annika; Eriksson, Monika; Meisingset, Erling L.; Solberg, Erling J.; Rolandsen, Christer M. (Zenodo, 2023)
Coprophagy, the eating of feces, has been documented in a wide range of species but appears to be rare or difficult to detect in deer (Cervidae). Here, we report the first observation of coprophagy in moose Alces alces , which was recorded using camera collars on free-ranging moose in Norway. The footage shows an instance of allocoprophagy by an adult female moose in spring (May). We summarize the current knowledge about coprophagy in deer and briefly discuss potential drivers and possible implications for disease transmission. Further research is needed to determine if coprophagy occurs frequently in moose and whether this behavior is positive (e.g., increased intake of nutrients) or negative (increased infection by parasites or pathogens). Any software capable of playing mp4-video files (e.g., Windows Media Player, Quicktime Player, VLC Player), Funding provided by: Naturvårdsverket Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100004357 Award Number: 2020-00108 Funding provided by: Naturvårdsverket Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100004357 Award Number: 2021-00032 Funding provided by: Svenska Jägareförbundet Crossref Funder Registry ID: http://dx.doi.org/10.13039/100009588 Award Number: 5909/2021 Funding provided by: Svenska Forskningsrådet Formas Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100001862 Award Number: 2020-01341 Funding provided by: Norges Forskningsråd Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100005416 Award Number: Project no 248194 Funding provided by: Framsenteret Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100022349 Award Number: Funding provided by: Miljødirektoratet Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100008776 Award Number: